Could recurrent painful ophthalmoplegic neuropathy be caused by a neurovascular conflict?: A case report - Karl Bjørnar Alstadhaug; Grete Bakkejord; Hans Kristian Bø (SAGE Publishing, 2023)
Objective: Describe and discuss a typical case with recurrent painful ophthalmoplegic neuropathy (RPON), and demonstrate a likely extrinsic compression of the sixth cranial nerve by a vascular loop. Background: RPON is a rare, but well-known entity, characterized by attacks of ophthalmoplegia associated with ipsilateral headache. The etiology is unknown, but a neurovascular conflict (NVC) has been suggested as a cause. Method: A 62-year-old woman presented in the emergency department with a horizontal diplopia that developed a few hours after the onset of a left temporal headache. In the past she had presented to the clinic with the same problem several times. She had been thoroughly examined, but no cause had been found. The symptoms had resolved by themselves. In addition to a classic finding in RPON, gadolinium enhancement and thickening of a cranial nerve, the new MRI scanning detected an NVC. Herein we discuss the relevance of this finding. Conclusion: A neurovascular conflict causing inflammatory demyelination of a single cranial nerve and relapsing remitting painful ophthalmoplegic neuropathy is an alluring idea. However, it is hard to conceive theoretically, and more reported cases with compelling data are needed to give credibility to such an idea.